Karakterisasi dan Identifikasi Bakteri Enterobacteriaceae pada Telur Penyu Lekang (Lepidochelys olivacea) asal Lhok Pante Tibang, Banda Aceh - Risa Nursanty *, Widya Sari, Safranita Risa Nursanty *, Widya Sari, Safranita; Widya Sari; Safranita Safranita (Jurnal Sain Veteriner, 2019)
The population of olive ridley turtle (Lepidochelys olivacea) are currently thretened with extinction, among the contributing factors is the failure of turtle eggs to hatch. The condition can be caused by the presence of bacterial contamination, especially group Enterobacteriaceae. The purpose of this research was to isolate the group of Enterobacteriaceae bacteria from olive ridley turtle. The sample used were shells from olive ridley turtle eggs comes from natural captivity in Lhok Pante Tibang Beach, Banda Aceh. The research parameters included the number of isolates, macroscopic morphology (shape, edge, elevation, and color of isolates), cell morphology (Gram staining and cell shape), and biochemical tests. Isolation method using spread plate and quadrant method. The isolation results obtained five isolates which had varying macroscopic morphology. The five isolates were Gram negative and formed such as trunk. Identification results found that there were three genus from Enterobacteriaceae videlicet two isolates were Enterobacter, two isolates as Shigella and the other were Klebsiella.